Large-Scale Assessment of Health-Related Physical Fitness in French Older Adults: Feasibility and Validity - Mack-Inocentio, Damien; Menai, Mehdi; Doré, Eric; Doreau, Bastien; Gaillard, Camille; Finaud, Julien; Pereira, Bruno; Duché, Pascale (Frontiers in Public Health, 2020)
Objectives: To assess the validity, internal consistency, implementation and feasibility of a sequence of tests, the Vitality Test Battery, designed to measure physical fitness, at a large scale in French older adults. Methods: 528 volunteers (age > 60 years) took the battery of 10 tests: 6-minute walk, trunk strength, hand-grip strength, medicine-ball throwing, 30-second chair stand, flexibility, balance, plate-tapping, ruler drop, and dual task. Results: Internal consistency was high, with the Cronbach alpha coefficients at around 0.77, explaining 64% of the variance. The test-retest correlations (0.3–0.6) between the items were acceptable and displayed an internal consistency property. Although five components explained 65% of the variance, all the items were kept because their eigenvalues were near to 0.9. External consistency was validated by a significant decrease in fitness scores (p < 0.001) with age and BMI. Discussion: The Vitality Test Battery is a safe, valid tool for assessing physical fitness in persons aged over 60 years.